Antidiabetic drugs restore abnormal transport of amyloid-β across the blood–brain barrier and memory impairment in db/db mice. (February 2016) - Chen, Fang; Dong, Rong Rong; Zhong, Kai Long; Ghosh, Arijit; Tang, Su Su; Long, Yan; Hu, Mei; Miao, Ming Xing; Liao, Jian Min; Sun, Hong Bing; Kong, Ling Yi; Hong, Hao
Abstract: Previous studies have shown significant changes in amyloid-β (Aβ) transport across the blood–brain barrier (BBB) under diabetic conditions with hypoinsulinemia, which is involved in diabetes-associated cognitive impairment. Present study employed db/db mice with hyperinsulinemia to investigate changes in Aβ transport across the BBB, hippocampal synaptic plasticity, and restorative effects of antidiabetic drugs. Our results showed that db/db mice exhibited similar changes in Aβ transport across the BBB to that of insulin-deficient mice. Chronic treatment of db/db mice with antidiabetic drugs such as metformin, glibenclamide and insulin glargine significantly decreased Aβ influx across the BBB determined by intra-arterial infusion of 125 I-Aβ1-40, and expression of the receptor for advanced glycation end products (RAGE) participating in Aβ influx. Insulin glargine, but not, metformin or glibenclamide increased Aβ efflux across the BBB determined by stereotaxic intra-cerebral infusion of 125 I-Aβ1-40, and expression of the low-density lipoprotein receptor related protein 1 (LRP1) participating in Aβ efflux. Moreover, treatment with these drugs significantly decreased hippocampal Aβ1-40 or Aβ1-42 and inhibited neuronal apoptosis. The drugs also ameliorated memory impairment confirmed by improved performance on behavioral tasks. However, insulin glargine or glibenclamide, but not metformin, restored hippocampal synaptic plasticity characterized by enhancing in vivo long-term potentiation (LTP). Further study found that these three drugs significantly restrained NF-κB, but only insulin glargine enhanced peroxisome proliferator-activated receptor γ (PPARγ) activity at the BBB in db/db mice. Our data indicate that the antidiabetic drugs can partially restore abnormal Aβ transport across the BBB and memory impairment under diabetic context. Highlights: Antidiabetic drugs partially restore abnormal transport of Aβ across the BBB. Antidiabetic drugs reduce Aβ levels in brain of db/db mice. Antidiabetic drugs inhibit Aβ-induced apoptotic responses in brain of db / db mice. Antidiabetic drugs ameliorate memory impairment in db / db mice.